Inhibited Solutions for Wells in Complicated Geological Conditions in the Areas of South-Western Turkmenistan - Deryaev, Annaguly (Anuário do Instituto de Geociências, 2024)
Shortcomings in methods for assessing the condition and composition of clayey rocks and shales lead to lower drilling cycle rates and profits and do not allow for proper quality of well construction in difficult geological conditions. The purpose of this study was to develop an optimal method of selecting the drilling mud composition when drilling wells in clay rock deposits. The following methods were used in the study: method of X-ray diffraction analysis of clay minerals; comparative analysis; method of mathematical statistics; side-tracking method. It was found that at equal wetting ability of clays, the fixing properties of the ALCAR-1 system are 3.5-4 times higher than those of the lime-potash system. Thus, with the same degree of stability, the water yields as well as drilling speeds may be higher with ALCAR than with the lime-potash system. The study of clayey rocks from the section of well No. 5 in the Bugdaily area showed that they have colloidality high enough for deep-seated clays, as they have a high content of montmorillonites. Drilling mud characterisation study found that mud samples No. 1, 2, and 3 had a strong inhibitory effect. The most effective sample was No. 3, which was able to ensure a stable state of clayey rocks for 90-100 days. The study of interaction of drilling fluid system ALCAR-3 with clayey rocks, carried out in the fields of south-western Turkmenistan, found that the inhibitory effect of the No. 3 sample can be further enhanced by the addition of 3% potassium chloride. The findings of this study can be used for successful drilling operations of deep wells in the areas of fields with complicated conditions associated with wellbore instability in the preparation of inhibited drilling fluids.